Atomistic simulation of amorphization during AlN nanoindentation. Issue 11 (1st June 2021) - Luo, Xing; Zhang, Zhibo; Xiong, Yongnan; Shu, Yao; He, Jiazhen; Zheng, Kaihong; Bao, Yuan; Urbassek, Herbert M.
Abstract: Molecular dynamics simulation is used to study phase transformations during nanoindentation into the (0001) surface of monocrystalline AlN with wurtzite structure. With the indentation depth increasing, the following effects are observed consecutively: a Y-type tearing of the surface; nucleation and growth of a graphite-like phase; formation and flow of an amorphous phase; generation of tetragonal intermediate structure. Due to the symmetry of the crystal structure, a Y-type groove appears after the surface is torn under the force induced by the indenter. Later, graphite-like phase nucleates near the peak of the Y-type groove due to stress concentration, and then expands into the deformation zone where the normal force plays the dominant role. Subsequently, the normal force, exerted to the graphite-like phase, increases continuously and thus induces amorphization. The amorphous phase, appearing beneath the indenter, grows and flows laterally, and leads eventually to the generation of a tetragonal intermediate structure. The results are unaffected when the speed is varied in a wide range of 10–160 m/s.